Pluripotent human embryonic stem cell derived neural lineages for in vitro modelling of enterovirus 71 infection and therapy - Yap, May Shin *; Tang, Yin Quan *; Yeo, Yin *; Lim, Wei Ling *; Lim, Lee Wei; Tan, Kuan Onn *; Richards, Mark; Othman, Lekhsan; Poh, Chit Laa *; Heng, Alexis Boon Chin * (BioMed Central, 2016)
The incidence of neurological complications and fatalities associated with Hand, Foot & Mouth disease has increased over recent years, due to emergence of newly-evolved strains of Enterovirus 71 (EV71). In the search for new antiviral therapeutics against EV71, accurate and sensitive in vitro cellular models for preliminary studies of EV71 pathogenesis is an essential prerequisite, before progressing to expensive and time-consuming live animal studies and clinical trials. This study thus investigated whether neural lineages derived from pluripotent human embryonic stem cells (hESC) can fulfil this purpose. EV71 infection of hESC-derived neural stem cells (NSC) and mature neurons (MN) was carried out in vitro, in comparison with RD and SH-SY5Y cell lines. Results: Upon assessment of post-infection survivability and EV71 production by the various types, it was observed that NSC were significantly more susceptible to EV71 infection compared to MN, RD (rhabdomyosarcoma) and SHSY5Y cells, which was consistent with previous studies on mice. The SP81 peptide had significantly greater inhibitory effect on EV71 production by NSC and MN compared to the cancer-derived RD and SH-SY5Y cell lines. Hence, this study demonstrates that hESC-derived neural lineages can be utilized as in vitro models for studying EV71 pathogenesis and for screening of antiviral therapeutics.